GW24-e3170 Angiotensin-(1-7) downregulates angiotensin II type 1 receptor and inhibites mechanical stress-induced cardiomyocyte autophagy. (1st October 2013) - Li, Lin; Liu, Xuebo; Xu, Jianfeng; Weng, Liqing; Ge, Junbo; Zou, Yunzeng
Abstract : Objectives: The renin-angiotensin system peptides are critically involved in the regulation of autophagy. Angiotensin-(1-7) [Ang-(1-7)] has many beneficial effects in the cardiac remodelling. Here, we tested the hypothesis that Ang-(1-7) has a protective role against the autophagy. Methods: Mechanical stress was imposed to cultured cardiomyocytes or heart of mice by in vitro mechanical stretch (MS) or in vivo transverse aorta constriction (TAC) procedures, respectively. Cardiac hypertrophy was evaluated by echocardiography, morphology, immunohistochemistry or animo acid-incorporation rate. Cardiomyocyte autophagy was determined by detecting the expression of LC3b using immunofluorescence staining and Western blot analysis. Results: MS for 24 hrs and TAC for 4 weeks induced significant in vitro and in vivo cardiac hypertrophy, respectively. Meanwhile, LC3b expression in cardiomyocyte was remarkably upregulated, suggesting the accompanied autophagy with cardiac hypertrophy after mechanical stress. Ang-(1-7) significantly reduced not only cadiomyocyte hypertrophy but also autophagy. Furthermore, MS induced upregulation of AT-R expression either in cultured cardiomyocytes or in hearts of mice and Ang-(1-7) significantly suppressed the upregulation of AT1-R. Conclusions: Our results suggest that Ang-(1-7) may abrogate MS-induced cardiac hypertrophy through downregulation of AT1-R expression.